Daurinol blocks breast and lung cancer metastasis and development by inhibition of focal adhesion kinase (FAK) - Woo, Jong Kyu; Jung, Hyun Jin; Park, Ji-Youn; Kang, Ju-Hee; Il Lee, Byung; Shin, Dong Yun; Nho, Chu Won; Cho, Soo-Young; Seong, Je Kyung; Oh, Seung Hyun (IMPACT JOURNALS LLC, 2017)
FAK overexpression has been reported in diverse primary and metastatic tumor tissues, supporting its pro-tumorigenic and pro-metastatic roles. Therefore, we have developed a neo-treatment strategy using daurinol to effectively treat cancer metastasis. Daurinol blocked cancer cell migration and invasion in vitro and exhibited anti-metastatic activity in an experimental metastasis model of breast and lung cancer. Daurinol selectively inhibited phosphorylation of FAK at Tyr925, Tyr576/577, and Tyr397 sites in a dose- and time-dependent manner. Daurinol effectively suppressed migration and invasion of MDA-MB-231 and A549 cancer cells. These data were associated with inhibition of expression and secretion of invasion factors, including matrix metalloproteinase (MMP) 2, MMP9, and urokinase plasminogen activator (uPA). Consistent with these in vitro results, daurinol (10 mg/kg; Oral gavage) effectively inhibited breast and lung cancer metastasis in a mouse model. In addition, daurinol showed strong suppressive activity of cell survival as revealed by colony formation assays. Analysis of cellular phenotypes revealed that inhibition of FAK phosphorylation in cancer cells limited colony formation, cell migration, and invasion, thereby reducing the cell proliferation rate. Furthermore, daurinol significantly reduced tumor development in 4-(methylnitrosoamino)-1-(3-pyridyl)-1- butanone (NNK)/benzo(a) pyrene (BaP)-treated A/J mice. Our results suggest that daurinol suppresses lung metastasis through inhibition of migration and survival via blockade of FAK activity.
Keywords: EPITHELIAL-MESENCHYMAL TRANSITION; THYROID-CANCER; E-CADHERIN; CELL-MIGRATION; COLON-CANCER; MOUSE MODEL; EXPRESSION; GROWTH; ACTIVATION; CARCINOMA